Cross-Cultural Collaboration in Quality Education for Sustainable Development: A Case of Indonesia and Thailand - Tri Widayatsih; Misdalina; Nurkardina Novalia; David Budi Irawan; Sukardi; Dian Mutiara; Yudi Irwansi; Nuryanti Permatasari (Jurnal Abdimas Cendekiawan Indonesia, 2025)
This paper presents an initiative that fosters cross-cultural collaboration between Indonesia and Thailand to promote quality education aligned with the Sustainable Development Goals (SDGs), particularly Goal 4. The program, implemented over four cycles, engaged 263 participants from 115 universities during its recent editions. It was carried out in cooperation with the Indonesian Embassy in Kuala Lumpur, PPI UPSI Malaysia, and several universities from both countries. The initiative emphasizes the practical application of science, technology, and innovation to address real-life challenges within international communities. A key aspect of this program involved on-site activities at Lukmanulhakeem School in Yala, Thailand, where students and faculty from Universitas PGRI Palembang and collaborating institutions worked directly with local communities. The outcomes highlight the value of such programs: students and lecturers enhance their leadership, communication, and teamwork skills; universities gain international exposure and institutional benefits; and local communities receive support through educational empowerment and problem-solving initiatives, especially for Indonesian migrant workers (PMI). This collaborative effort not only supports global education goals but also builds a foundation for ongoing international engagement that benefits higher education institutions, policymakers, and underserved communities alike. The program stands as a replicable model for sustainable, inclusive educational partnerships across borders.